UNLOCKING SCIENCE DIPLOMACY’S HIDDEN POWER: THE ROLE OF SCIENCE DIPLOMACY IN THE NEGOTIATION OVER THE ALPART REFINERY IN JAMAICA - Oliveira, Amancio Jorge Silva de (2023)
This article delves into the relationship between Science Diplomacy (SD) and multilateral negotiations, with a specific case study focusing on aluminum production in Jamaica. It highlights the often indirect yet pivotal role of SD in shaping the outcomes of negotiations concerning energy and environmental issues. Although the concept of SD is not always directly at the negotiation table, SD practices act as a bridge between the scientific community and policymakers. The case study analyzes the influence of SD on negotiations related to alumina production in Jamaica, specifically the sale of the Alpart alumina refinery in 2016. It demonstrates how SD diverted negotiations from solely political and commercial considerations to technical discussions on environmental impacts. The crisis initially centered around a coal-based power plant and eventually extended to bauxite extraction, revealing the critical role of affordable energy in aluminum refining. Methodologically, our research design follows the traditional guidelines of a descriptive case study. We employed concepts extracted from both the theory of negotiations and science diplomacy. Leverage power and interests of key actors, including JISCO (Jinquan Iron and Steel Company), the Jamaican government, and the Jamaica Environment Trust (JET), are dissected. Ultimately, it underscores the influence of SD practices on the negotiations, shifting the focus towards environmental concerns and highlighting the importance of informed decision-making in international negotiations. JET played a pivotal role by illuminating the environmental hazards and by influencing the redefinition of power dynamics in the negotiations. Thus, this work exemplifies how SD can reshape negotiations and foster sustainable solutions to complex global challenges.